Numerical analysis of the flexural characteristics of the profiled steel sheeting dry board (PSSDB) floor system using Finite Element - Marwan Al-Shaikhli; Fawzi Khalaf (Journal of Madenat Alelem University College, 2023)
The purpose of this paper is inspecting the flexural performance of Profiled Steel Sheeting Dry Board (PSSDB) floor system. A lightweight composite slab consists of a steel deck connected to a dry board using self-tapping and self-drilling screws. The study employed Finite Element (FE) modelling using ABAQUS software. The results were validated with experimental ones, and it has demonstrated the adequacy of the FE model to simulate the performance of the floor panel. Thereafter, three parametric studies were suggested in order to understand the influencing parameters. It is shown that the depth of the dry board can improve the load capacity by no more than 7.5%, while the thickness of steel deck has an enhance it by up to 65%. Finally, it was established that the type of profiled steel sheeting can affect the stiffness and load capacity by up 18%.